Young people’s proposals for tackling everyday challenges in order to improve mental health: a qualitative comparison study based on different socioeconomic neighborhoods - Helena Gard; Karin Ingvarsdotter; Gabriella Elisabeth Isma; Karin Enskär; Elisabeth Mangrio (BMC Public Health)
Abstract Background Everyday challenges and stress negatively affect young people’s mental health. Socioeconomic status (SES) is associated with different stressors and different stress-coping mechanisms. Many interventions target youth mental health, but few consider socioeconomic differences in the planning, implementation, or evaluation. In a Swedish context socioeconomic status is related with migration experience. The aim of the study was to explore proposals for tackling everyday challenges among young people from different socioeconomic neighborhoods. Methods Eight focus groups, with participants between 13 and 15 years old from eight schools, were conducted in the south of Sweden. The participants discussed proposals for tackling everyday challenges. Using comparative thematic analysis, the focus group transcripts were divided into two groups, based on the socioeconomic status of the school’s neighborhood, and analyzed comparatively. Most of the participants in low SES neighborhoods had foreign background and most of the participants in high SES neighborhoods were Swedish born. Results The analysis resulted in four shared themes between the two SES groups: society is responsible, school is responsible, parents are responsible, and I am responsible. The differences and similarities between the two groups are presented in sub-themes. Many of the proposals were similar between the two SES groups, but with different underlying issues and examples. Conclusion Both groups proposed that adults must listen more to young people in order to improve the everyday challenges young people face. However, the low SES group in general expressed both more frustration and more agency, compared to the high SES group. This could be important to consider when planning school-based mental health promotion in different socioeconomic neighborhoods.